Palatal Rugae Pattern in Nepalese Subjects - Bajracharya, Dipshikha; Vaidya, Anisha; Thapa, Sunaina; Shrestha, Sujita (Orthodontic Journal of Nepal, 2013)
Objective: To determine the number and pattern of palatal rugae in Nepalese subjects and to find the association of gender with the number and pattern of palatal rugae. Materials & Method: 200 Nepalese subjects comprising of 100 male and 100 female were randomly selected and their maxillary casts were examined for the palatal rugae length applying the classification proposed by Thomas and Kotze and palatal rugae pattern was recorded using the classification given by Kapali. Statistical analysis using Student t-test was applied for comparing the number of palatal rugae between right and left sides. Chi square test was used to find the association between gender and number of rugae as well as the pattern. Result: The study demonstrated that the mean number of primary palatal rugae on left side was predominant, similarly wavy pattern was the most predominant in Nepalese subjects. No statistical significant difference was noticed in the palatal rugae number and pattern between the gender groups. Conclusion: The study found predominant palatal form in Nepalese subjects which might have superior effectiveness in population differentiation and may be used as an effective tool in forensic odontology identification.